EVALUASI MANAJEMEN LABORATORIUM KOMPUTER PADA PAKET KEAHLIAN TKJ DI SMK KABUPATEN WONOGIRI - Antonius Edy Setyawan; Thomas Sukardi (VOX EDUKASI: Jurnal Ilmiah Ilmu Pendidikan, 2018)
The research aims to describe the effectiveness of computer laboratory management on Computer and Networking Engineering program at Vocational High Schools in Wonogiri Regency from Context, Input, Process and Product aspects. This was an evaluation study employing the quantitative approach. The evaluation model employed was the CIPP (Context, Input, Process, Product) that was suggested by Stufflebeam. The respondents consisted of 9 headmasters, 9 infrastructure vice principals, 9 heads of program, 4 heads of the computer laboratory, 3 technicians, 21 teachers and 225 students of class XI. The data analysis technique used was the descriptive statistics using the SPSS software IBM 23 version.The results of the research show that: (1) based on context aspect, the effectiveness of computer laboratory management on Computer and Networking  Engineering program at Vocational High Schools in Wonogiri Regency is good with a score 84.19%; (2) based on input aspect the effectiveness of computer laboratory management on Computer and Networking  Engineering program at Vocational High Schools in Wonogiri Regency is good with a score 79.69%; (3) based on process aspect  the effectiveness of computer laboratory management on Computer and Networking  Engineering program at Vocational High Schools in Wonogiri Regency is good with a score 84.17%; and (4) based on product aspect  the effectiveness of computer laboratory management on Computer and Networking  Engineering program at Vocational High Schools in Wonogiri Regency is good enough with achievement a score 69.41%.